Xenpozyme: a revelation for Neiman-Pick disease - Khan, Ariyan; Kamaluddin Khan, Khaja (International Journal Of Community Medicine And Public Health, 2023)
Nieman-Pick disease (NPD) also known as acid sphingomyelinase deficiency (ASMD) is a rare autosomal recessive disorder of lysosomal storage which affects 1 in 250,000 individuals mainly belonging to the Ashkenazi Jew population. The prevalence varies across the three main subtypes where type A and B affects 1 in 40,000 and type C affects 1 in 150,000 individuals, being more prevalent in the French-Acadian descent in the region of Nova Scotia.